Exon 2 sequencing of the new HLA‐DRB1 allele, DRB1*13:216. (6th January 2017) - Planelles, D.; Balas, A.; Alenda, R.; Vicario, J. L.
Summary: A novel HLA‐DRB1*13:216 allele was characterized in a Spanish bone marrow donor.